1980
DOI: 10.1002/j.1537-2197.1980.tb07638.x
|View full text |Cite
|
Sign up to set email alerts
|

Response of Bush Bean Exposed to Acid Mist

Abstract: Bush bean plants (Phaseolus vulgaris L. cv. Contender) were treated once a week for six weeks with simulated acid mist at five pH levels ranging from 5.5 to 2.0. Leaf injury developed on plants exposed to acid concentrations below pH 3 and many leaves developed a flecking symptom similar to that caused by ozone. An adaxial, interveinal bleached area resembling SO2 injury also developed on some trifoliate leaves at the low pH treatments. Microscopic observation of injured trifoliates indicated that the palisade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…However, as the number of daily rainfall exposures increases, the changes in rates of leaching and accumulation of specific nutrients become more striking, and significant alterations in resistance to gas exchange become evident. The results of this study complement and extend those of previous experiments on the effects of simulated acidic rain on plant foliage (Wood and Bormann, 1975;Fairfax and Lepp, 1975;Ferenbaugh, 1976;Hindawi et al, 1977). Hindawi, Rea and Griflfis (1980) demonstrated lower contents of nitrogen, calcium, magnesium, and phosphorus in foliage of Phaseolus vulgaris L. exposed to simulated acid mist.…”
Section: Discussionsupporting
confidence: 79%
“…However, as the number of daily rainfall exposures increases, the changes in rates of leaching and accumulation of specific nutrients become more striking, and significant alterations in resistance to gas exchange become evident. The results of this study complement and extend those of previous experiments on the effects of simulated acidic rain on plant foliage (Wood and Bormann, 1975;Fairfax and Lepp, 1975;Ferenbaugh, 1976;Hindawi et al, 1977). Hindawi, Rea and Griflfis (1980) demonstrated lower contents of nitrogen, calcium, magnesium, and phosphorus in foliage of Phaseolus vulgaris L. exposed to simulated acid mist.…”
Section: Discussionsupporting
confidence: 79%
“…Analysis of leaf element concentrations before and after exposure to acidic rains and mists has shown that acid-induced ion effluxes can reduce foliar P, K, Ca, and Mg (Blanpied, 1979;Hindawi, Rea & Griffis, 1980;Jacobson et al, 1989). Detectable depletion is more likely in plants of low nutritional status than in plants with adequate nutrition (Leonardi & Fluckiger, 1989;Turner & Tingey, 1990).…”
Section: Evidence For Depletion Of Foliar Elementsmentioning
confidence: 99%
“…Reduced levels of pigments due to acidic wet deposition have been frequently reported (e.g. Ferenbaugh, 1976;Hindawi, Rae & Giffis, 1980;Jakhola et al, 1980) but processes such as photosynthesis and respiration have been shown to be positively affected only at unrealistically low pH levels around pH 2 (F"erenbaugh, 1976).…”
Section: Introductionmentioning
confidence: 99%